2017
DOI: 10.1111/jan.13333
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in paediatric intensive care nurses part 1: Behavioural and psychological correlates

Abstract: Paediatric intensive care work demands, such as patient pain exposure, may be associated with nurse's higher report of empathy and pain in self and others, but also with higher levels of secondary trauma and burnout, when compared with allied health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 61 publications
1
24
0
1
Order By: Relevance
“…Similarly, in a study on determining the communication skills and empathy levels of students attending health sciences faculty, the empathic tendency score of the group who stated they had difficulties in patient relations was 67.2, while the empathic tendency score of the group that stated that they did not have difficulties in patient relations was 70.0. Although this relationship was concluded to be statistically insignificant, the empathic tendency scores of the group that stated they had no problems in patient relations were higher than those of who had difficulties . Similarly, this study found that the empathic tendency scores of the dietitians who achieved being empathic, managed to establish communication with patients, understood and attached importance to the feelings and thoughts of patients were higher ( P < 0.05).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, in a study on determining the communication skills and empathy levels of students attending health sciences faculty, the empathic tendency score of the group who stated they had difficulties in patient relations was 67.2, while the empathic tendency score of the group that stated that they did not have difficulties in patient relations was 70.0. Although this relationship was concluded to be statistically insignificant, the empathic tendency scores of the group that stated they had no problems in patient relations were higher than those of who had difficulties . Similarly, this study found that the empathic tendency scores of the dietitians who achieved being empathic, managed to establish communication with patients, understood and attached importance to the feelings and thoughts of patients were higher ( P < 0.05).…”
Section: Discussionmentioning
confidence: 56%
“…In these papers, which were generally informed by cognitive psychology, empathy was seen as a type of emotional contagion or an automatic mirroring of the neural responses of another person. In one study that used functional magnetic resonance imaging (fMRI), it was identified that nurses experienced an automatic and subconscious resonance with patients' pain that activated the same physiological sensations in the nurse as in the patient and triggered other attributes of empathy (Latimer et al, ). This finding is supported by previous neuroscientific studies that used fMRI studies to identify automatic activation of empathy‐related brain networks in response to the distress of another person (Hein, Silani, Preuschoff, Batson, & Singer, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ozcan et al (, p. 135) referred to nursing students' ability to imagine themselves in another person's place and to look at events from that person's point of view; and McKinnon (, p. 3891) found that empathy requires the ability to imagine and represent the imagined perception within the self. Two papers (Cliffordson, ; Latimer et al, ) also included the notion of “fantasy,” one of the subscales of the Interpersonal Reactivity Index (IRI) (Davis, , p. 119), and described as the tendency to imaginatively transpose oneself into fictional situations or to identify with fictional characters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present paper is Part 2 of a set of papers reporting the results of a study of empathy for pain in paediatric nurses. Knowing that paediatric nurses rated infant and adult pain significantly higher than a comparison group of allied health professionals (AHPs; Part 1, Latimer et al, 2017), this paper focuses on the neuroimaging results; comparing the brain response during pain assessment in these same participants.…”
Section: Introductionmentioning
confidence: 99%